2017
DOI: 10.1590/1413-81232017221.10342015
|View full text |Cite
|
Sign up to set email alerts
|

Acupuntura no Sistema Único de Saúde – uma análise nos diferentes instrumentos de gestão

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 14 publications
0
5
0
9
Order By: Relevance
“…In the research, it was identified the absence of records regarding acupuncture in 84.4% of Municipal Health Plans. 18 There is a lack of knowledge and even insecurity of managers in the definition of ICP, as they mentioned biomedical practices. This aspect corroborates both the conceptual inaccuracy (confusing and masking reality), as well as the demonstration of fragility in the institutionalization, evaluation and monitoring of these practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the research, it was identified the absence of records regarding acupuncture in 84.4% of Municipal Health Plans. 18 There is a lack of knowledge and even insecurity of managers in the definition of ICP, as they mentioned biomedical practices. This aspect corroborates both the conceptual inaccuracy (confusing and masking reality), as well as the demonstration of fragility in the institutionalization, evaluation and monitoring of these practices.…”
Section: Discussionmentioning
confidence: 99%
“…23 Such challenges have as potential obstacle the underfunding in the three spheres of management. 18,20 Another research on the experience of the Lian Gong's insertion in the Samambaia FHS (Federal District) showed that the lack of adequate places and the need to train a larger number of professionals is the biggest problem of the work with that ICP. 33 In addition, insufficient systematized dissemination also makes it difficult to maintain ICP and, consequently, contributes to the non-acceptance of this holistic approach, which broadens the contextualization of regional specificities and relies on administrative, political and institutional planning for the construction of a prudent UHS.…”
Section: Integrative and Complementary Practicesmentioning
confidence: 99%
“…O profissional enfermeiro encontra-se mais atuante crescentemente e consistente de sua função, tendo oportunidade de explorar várias categorias terapêuticas ao desempenhar sua prática assistencial, executando alternativas de atenção ao enfermo para que, assim, não perca o desempenho de sua cidadania e autonomia. Tais alternativas acabam tornando o tratamento ofertado ao cliente mais prazeroso e menos sacrificante, sendo capaz até mesmo de diminuir o período de internação hospitalar, se houver a necessidade (SOUSA et al, 2017).…”
Section: Assistência De Enfermagem Na Acupunturaunclassified
“…Estes documentos, quando construídos de forma coletiva, ou seja, a partir dos estudos dos determinantes sociais em saúde, bem como dialogado com a comunidade, demonstram o compromisso político assumido ou não pelo gestor e sua equipe de gestão. Nessa perspectiva é que o estudo documental auxilia a análise de políticas públicas, na medida em que proporciona à investigação em uma fonte privilegiada de dados, uma vez que aprofunda e aproxima as ideias (Sousa et, 2017).…”
Section: Planejamento Em Saúde E Redes De Atençãounclassified